Keeping tabs: Attachment anxiety and electronic intrusion in high school dating relationships. (May 2016) - Reed, Lauren A.; Tolman, Richard M.; Ward, L. Monique; Safyer, Paige
Abstract: Social media have become significant contexts for dating relationships among high school students. These media, which allow for increased visibility of dating partners' information and constant connectivity, may put teens at risk for problematic digital dating behaviors. This study sought to replicate and expand on research with college students to examine the association between attachment insecurity (relationship anxiety and avoidance) and electronic intrusion in high school dating relationships. Electronic intrusion (EI) is the use of social media to intrude into the privacy of a dating partner, monitor a partner's whereabouts and activities, and pressure a partner for constant contact. A survey study of 703 high school girls and boys found that higher levels of attachment anxiety were associated with more frequent perpetration of EI for both girls and boys. Therefore, especially for anxiously attached teens, social media may create a "cycle of anxiety" in which social media serve as both a trigger for relationship anxiety and a tool for partner surveillance in an attempt to alleviate anxiety. Highlights: Electronic intrusion involves monitoring and privacy invasion using social media. Attachment anxiety positively associated with perpetrating electronic intrusion. Social media may increase risk for anxious teens to engage in electronic intrusion. Replicated and expanded on previous research on college students.